Influence of exposure to perinatal risk factors and parental mental health related hospital admission on adolescent deliberate self-harm risk - Nan Hu; Jianghong Li; Rebecca A. Glauert; Catherine L. Taylor (European Child & Adolescent Psychiatry, 2017)
Adolescent deliberate self-harm (DSH) has been found to be associated with a range of bio-psycho-social factors. Simultaneous investigations of these factors enable more robust estimation of the independent effect of a specific risk factor by adjusting for a more complete set of covariates. However, few studies have had the ability to examine all of these factors together. This study used the linkage of population-level de-identified data collections from government agencies to investigate a range of biological, psychological, and social risk factors and their effects on adolescent risk of DSH (with or without suicidal intent). The investigation was undertaken by progressively adjusting for plausible covariates, including fetal growth status and birth order, early familial social factors, parental hospital admissions due to psychiatric disorders or DSH, and parental all-cause death. Conditional logistic regression was used for data analysis. Children's psychiatric history was analysed to examine the extent to which it may account for the link between the risk factors and adolescent DSH risk. This study identified significant biological and perinatal social risk factors for adolescent DSH risk, including overdue birth, high birth order (≥2), single or teen/young motherhood, high neighbourhood socioeconomic disadvantage, and parental psychiatric and/or DSH-related hospital admissions. Further, parental psychiatric and/or DSH-related admissions, and children's psychiatric admissions in particular, largely attenuated the effects of the perinatal social risk factors but not the biological factors on adolescent DSH risk. These results highlight the importance of taking joint actions involving both health and social services in the prevention of adolescent DSH.
Keywords: 330; deliberate self-harm; social and biological risk factors; parental psychiatric disorders; data linkage